Black social movements in Latin America : from monocultural mestizaje to multiculturalism - Rahier, Jean Muteba, 1959- (Palgrave Macmillan, 2012)
This collection of essays aims to explore the transformations of the political landscapes within which Afro Latino social movements have been operating since the end of the 1970s. It is premised on the assertion that, distinctively in different national contexts, the major characteristic of these transformations has been the ideological alteration of the official narrative of national identity through the passage from 'monocultural mestizaje' and 'invisibilization' of Afro Latinos organized by the state and other dominant social actors to multiculturalism and state corporatism/cooptation. Every individual essay emphasizes the processes that led to the emergence of state corporatism/cooptation of Afro Latinos and their consequences on Afro Latino social movements. As many of the contributions show, these new situations have rendered Afro Latino political struggles more complex. Sometimes, as in the case of the Pacific Lowlands of Colombia, they have heightened to new levels of aggressiveness dominant socio-political actors' antagonism towards them.